Intestinal obstruction in cystic fibrosis: a surgeon’s perspective - Odofin, Ayodeji (International Surgery Journal, 2018)
Background: Distal intestinal obstruction syndrome(DIOS) is one of the commonestgastrointestinal manifestation of Cystic Fibrosis. It occurs as a result ofimpaction of mucofeculent material in the ileocaecum and ascending colon. Themedical management is effective in the chronic presentation, but the optimummanagement in the acute presentation is still a grey area.The aim of this study is to retrospectively follow up patients presenting withfeatures of DIOS who had surgical resection of the ileocaecum to assess thelong-term outcome in terms of recurrence of symptoms. Methods: Case notes of eight patients presenting with features of acute DIOS between 2000 and 2006 were retrieved from the Cystic fibrosis unit of a tertiary teaching hospital and analysed. Results: Eight patients were included in this study, male: female ratio of 5:3age range: 18-24. Acute presentation: 6, elective presentation:2. The mainpresenting features were abdominal pain, constipation, vomiting and RIF mass.Six patients had ileocaecectomy; one had a small bowel resection and one anextended right hemicolectomy.Six patients had no further symptoms of DIOS four years post-surgery, two hadfurther symptoms with one requiring further surgery. Conclusions: Ileocaecal resection in patients presenting with acute DIOS is aviable and effective option in management.